The Influence of Paternal Spirituality and Attachment on Boys’ and Girls’ Characters in Junior High School - Fannisa Septariana; Dwi Hastuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
Proper parenting reflected on the goodness of parental spirituality and attachment in which affected adolescents' character development. The research was aim to examine the influence of paternal spirituality and attachment towards adolescents' character. This study used a cross-sectional study design which involved 84 respondents from one of the public high school in Bogor City and consisted of 37 boys and 47 girls, samples were chosen by cluster random sampling technique. Data were analyzed descriptively, independent t-test, Pearson correlation, and multiple linear regression. Data was gathered by self-report questionnaires. The research found that paternal spirituality and attachment had a better score than the boys. Also, politeness and perseverance characters of girls better than the boys. Moreover, the better paternal spirituality and attachment the better character of adolescents. The result of the multiple linear regression test shows that paternal spirituality and attachment became the main factors in affecting adolescents' character in junior high school.